2012
DOI: 10.4085/1062-6050-47.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences, Hormone Fluctuations, Ankle Stability, and Dynamic Postural Control

Abstract: Although women presented with more ankle inversion-eversion laxity and less dynamic postural control, hormonal fluctuations during the menstrual cycle (preovulatory compared with postovulatory) did not affect ankle laxity or dynamic postural control, 2 factors that are associated with ankle instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 34 publications
1
58
2
Order By: Relevance
“…Some studies have shown no difference between males and females in dynamic balance and tandem gait. 23,24 However, our findings were consistent with others showing that females had less dynamic postural control 25 and walked more slowly than males. 26 Potential reasons for sex differences in dynamic balance include differences in muscle strength and the speed of muscle contractions.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have shown no difference between males and females in dynamic balance and tandem gait. 23,24 However, our findings were consistent with others showing that females had less dynamic postural control 25 and walked more slowly than males. 26 Potential reasons for sex differences in dynamic balance include differences in muscle strength and the speed of muscle contractions.…”
Section: Discussionsupporting
confidence: 92%
“…However, the exact variability of ankle laxity throughout the menstrual cycle remains controversial. In fact, Ericksen and colleagues showed no differences in ankle laxity or dynamic postural control according to hormonal fluctuations during the menstrual cycle (Ericksen and Gribble 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As estrogen peaks at ovulation, these measurement times may have masked the results. 23 Another contributor to sway may be the increased body temperature seen at ovulation. 33 This would also increase laxity in the plantar fascia and other tendons and ligaments and contribute to the increased sway as tendons and ligaments are highly susceptible to small increases in temperature.…”
Section: Discussionmentioning
confidence: 99%